What Would Be Really Helpful but Nobody Ever Tells You: Five Key Recommendations Derived From Lessons Learned During a Qualitative Study in Clinical Settings. Issue 1 (March 2018) - Steele, Rose; Davies, Betty; Krueger, Guenther
The complexity of qualitative research can lead to a less thorough analysis than would be ideal. Even experienced researchers can become entwined in the myriad of decisions that must be made. Descriptions of qualitative approaches in numerous textbooks and published articles often lack sufficient details to help a researcher surface from the entanglements, especially when conducting studies in clinical settings. In this paper, we share our experiences of navigating some "real-world" issues in doing qualitative research. We describe five key, practical recommendations to assist researchers in preventing, or at least alleviating, some of the challenges that researchers may face, particularly ones that limit in-depth analysis: (1) conduct a pilot study, (2) hire a research analyst, (3) engage the "right" team, (4) attend to team cohesion, and (5) conduct conceptual analysis through a process of "node expansion."